Changes in swing high bar performance and coordination: Skill acquisition and fine tuning skill - Busquets Faciaben, A. (Universitat de Barcelona. Departament de Teoria i Història de l'Educació, 2010)
Numerous motor-perceptual tasks can be observed across the ages, especially if individuals are involved in sport activities. A person facing a novel task has to elaborate new movements to achieve the task goal (skill acquisition period). To become more successful and efficient, that is, to be an expert in a learned task, the subject must adjusts movement parameters depending on many constraints (fine tuning skill period). From a Dynamic System Theory perspective, movement arises from the relative impact of practice and constraints (organismic, task, and environmental). Focusing in the organismic constraints, the a-priory talent is a critical point for understanding motor learning in the skill acquisition period. In addition, the age of the performer must be specially considered in the fine tuning skill period due to the biological maturational and expertise processes taking place with time. The overarching goal of this thesis was to characterize both periods of learning (skill acquisition and fine tuning process) from a dynamical system theory perspective focusing in the longswing as a sport skill.